Abortion: A Review on Indonesia Regulations - Hariansi Panimba Sampebulu (Universitas Muhammadiyah Sidoarjo, 2019)
The position of women in legal construction in Indonesia today is still difficult to adjust to the circumstances that occur, especially in terms of equality issues. The abortion that has been a problem for so long time, being discussed because of the rules that are considered not in accordance with the existing rules, and the amount of pressure from various things. Law and Women are always placed in objects that are not neutral, especially in terms of discussing reproductive health. The government and legislation feel that they have a stake in integrating reproductive health owned by women. It is the position of women in the law that gives rise to many struggle movements and the diffusion of feminism in Indonesia. The rules of Article 31 paragraph 1 and 2 of Government Regulation Number 61 of 2014 which regulate safe abortion need to be more attention and safeguarded, so that a woman has the right to be based on herself.